The Myth of the Clash of Civilizations. - Bottici, Chiara (Routledge advances in Middle East and Islamic studies., 2013)
While globalization unifies the world, divisions re-emerge within it in the form of a spectacular separation between Islam and the West. How can it be that Huntington's contested idea of a clash of civilizations became such a powerful political myth through which so many people look at the world? Bottici and Challand disentangle such a process of myth-making both in the West and in Muslim majority countries, and call for a renewed critical attitude towards it. By analysing a process of elaboration of this myth that took place in academic books, arts and media, comics and Hollywood fi.